2010
DOI: 10.1016/j.msea.2010.03.094
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interface topography for Ultrasonic Consolidation of aluminium

Abstract: Ultrasonic Consolidation (UC) is an additive manufacturing technology which is based on the sequential solid-state ultrasonic welding of metal foils. UC presents a rapid and adaptive alternative process, to other metal-matrix embedding technologies, for 'smart' metal composite material production. A challenge that exists however relates to optimising, for bond density and plastic flow, the interlaminar textures themselves that serve as the contact surfaces between the foils. UC employs a sonotrode connected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…The topography that results from direct sonotrode-foil contact has been shown to have a marked effect on the interlaminar bonding dynamics of a UAM structure [28]. By measuring the change in surface roughness as a result of embedding both coated and uncoated fibers, it is possible to predict the bonding characteristics likely to result from depositing a fourth layer on top of the covering layer (see Section 3.4).…”
Section: Topography Of Aluminum Substrate and Embedded Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…The topography that results from direct sonotrode-foil contact has been shown to have a marked effect on the interlaminar bonding dynamics of a UAM structure [28]. By measuring the change in surface roughness as a result of embedding both coated and uncoated fibers, it is possible to predict the bonding characteristics likely to result from depositing a fourth layer on top of the covering layer (see Section 3.4).…”
Section: Topography Of Aluminum Substrate and Embedded Fibersmentioning
confidence: 99%
“…Direct imprint of the sonotrode topography onto the UAM substrate can lead to regions of intimate contact between upper and lower foils, which are indistinguishable from each other, but are not metallurgically bonded [28]. This can cause discrepancies in LWD analysis due to difficulties in differentiating these areas from genuinely bonded regions.…”
Section: Mechanical Peel Testingmentioning
confidence: 99%
“…In addition to these bond Figure 13.7 Schematic of the formation machines integrated machining centre. Typically, the greater the amplitude the higher the energy input into the foil-to-part interface during UAM; higher energy input has been shown to result in superior bond strength and greater plastic flow during USW (Friel et al, 2010a;Hopkins et al, 2011;Kong et al, 2004b;Li and Soar, 2009;Tuttle, 2007;Yang et al, 2009;Weare et al, 1960). Typically, the greater the amplitude the higher the energy input into the foil-to-part interface during UAM; higher energy input has been shown to result in superior bond strength and greater plastic flow during USW (Friel et al, 2010a;Hopkins et al, 2011;Kong et al, 2004b;Li and Soar, 2009;Tuttle, 2007;Yang et al, 2009;Weare et al, 1960).…”
Section: Sonotrode Oscillation Amplitudementioning
confidence: 99%
“…The modified topology of the sonotrode is necessary to efficiently transfer kinetic energy to the bond interface during the oscillations and weld pressure and to induce sufficient plastic flow for bonding (Friel et al, 2010a;Johnson, 2008;Johnson et al, 2011;Li and Soar, 2009). The roughened surface creates a mechanical coupling and prevents energy loss through slippage (Weare et al, 1960).…”
Section: Sonotrode Topologymentioning
confidence: 99%
“…Until now, research on high fibre volume integration has shown that the delivery of sufficient energy to the interfaces was insufficient and led to poor bonding quality. 7,12,13 To approach high volume fibre integration without high amplitudes yet reducing the required amount of plastic flow and secure and accurate placement of the fibres, a method based on creating trenches in post-UC samples via a laser was pursued. Figure 2 displays the schematic representation of the proposed method.…”
Section: Introductionmentioning
confidence: 99%